2021
DOI: 10.3390/biology10070681
|View full text |Cite
|
Sign up to set email alerts
|

Role of Persistent Organic Pollutants in Breast Cancer Progression and Identification of Estrogen Receptor Alpha Inhibitors Using In-Silico Mining and Drug-Drug Interaction Network Approaches

Abstract: The strong association between POPs and breast cancer in humans has been suggested in various epidemiological studies. However, the interaction of POPs with the ERα protein of breast cancer, and identification of natural and synthetic compounds to inhibit this interaction, is mysterious yet. Consequently, the present study aimed to explore the interaction between POPs and ERα using the molecular operating environment (MOE) tool and to identify natural and synthetic compounds to inhibit this association through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…The results showed that HBCD may be involved in the prevailing of breast cancer and may be one of the major contributors to its appearance given its interaction with the Erα protein. Thus, the authors conclude that for these results to be validated, in vitro and in vivo studies will be necessary [ 118 ].…”
Section: Studies In Humansmentioning
confidence: 99%
“…The results showed that HBCD may be involved in the prevailing of breast cancer and may be one of the major contributors to its appearance given its interaction with the Erα protein. Thus, the authors conclude that for these results to be validated, in vitro and in vivo studies will be necessary [ 118 ].…”
Section: Studies In Humansmentioning
confidence: 99%